Implementasi Monitoring Kualitas Udara Taman di Kota Malang menggunakan Low Power Mode pada Android berbasis Arduino Uno - Ananda Ribelta; Rizal Maulana; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Definition polution defilement related to the environment that is lived by humans. This defilement may caused by many factor examples are from gas emission in public transport and forest fire that is near with citizen lives. Solution is necessary to informed about ISPU anytime to people directly through their android smartphone. Time become important indicator in monitoring system, that monitoring system are activated and deactivated based time who ruled by government. In monitoring there is color which is strong indicator about environment around. Using low power mode to aimed a lower consume of electricity on the system then utilized the work principle of system which are in sleep condition and wake condition. Based test which has been done the coefficient of determination from read value MQ 131 sensor is 99,1% rated output voltage, MQ 136 in the amount of 98,5% rated output voltage and GP2Y1010AU0F sensor output voltage accuracy of 98%. Then for MQ 7 sensor average error of 18,55%. Furthermore there is system performance tests when power down sleep for 10 times and then testing on average to get 7,5% lower consumed energy by the system. Calculation from PPM value in to ISPU value had an accuracy 100%